Learning to think spatially. (National Academies Press, 2006)
Examines how spatial thinking might be incorporated into existing standards-based instruction across the school curriculum. Spatial thinking must be recognized as a fundamental part of K 12 education and as an integrator and a facilitator for problem solving across the curriculum. With advances in computing technologies and the increasing availability of geospatial data, spatial thinking will play a significant role in the information-based economy of the twenty-first century. Using appropriately designed support systems tailored to the K 12 context, spatial thinking can be taught formally to all students. A geographic information system (GIS) offers one example of a high-technology support system that can enable students and teachers to practice and apply spatial thinking in many areas of the curriculum.
Keywords: Space perception -- Study and teaching.; Geographic information systems.; Space perception.; Space Perception; Education; Geographic Information Systems; Perception spatiale -- Étude et enseignement.; Systèmes d'information géographique.; Perception spatiale.; geographic information systems.; space perception.; EDUCATION -- Educational Psychology.; Space perception; Geographic information systems; Space perception -- Study and teaching; Ruimtelijke waarneming.; Waarneming.; Geografische informatiesystemen.